1999
DOI: 10.2110/jsr.69.747
|View full text |Cite
|
Sign up to set email alerts
|

Recent sedimentary facies of isolated carbonate platforms, Belize-Yucatan system, Central America

Abstract: Distribution of recent sedimentary facies is significantly different in four closely spaced, isolated carbonate platforms off the coasts of Belize and Yucatan (SE Mexico). These differences are largely controlled by variations in submarine topography, which are likely the result of differential subsidence and karstification from platform to platform. A variety of depositional styles and patterns is found in platform interiors that developed during the same Holocene sea-level rise. Composition and texture of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(78 citation statements)
references
References 41 publications
2
76
0
Order By: Relevance
“…Radiocarbon age of carbonate sands has been used as an indicator of longevity, production rate, and transport of coastal sediments (Kench, 1997;Gischler and Lomando, 1999). Dates measured for Hawaiian coral and skeletal fragments show that sediment is produced, transported, and lost from the coastal system on a millennial scale.…”
Section: Beach Sedimentsmentioning
confidence: 99%
“…Radiocarbon age of carbonate sands has been used as an indicator of longevity, production rate, and transport of coastal sediments (Kench, 1997;Gischler and Lomando, 1999). Dates measured for Hawaiian coral and skeletal fragments show that sediment is produced, transported, and lost from the coastal system on a millennial scale.…”
Section: Beach Sedimentsmentioning
confidence: 99%
“…In a discussion of the sediment distribution of three isolated carbonate platforms seaward of the Belize barrier reef system (Glovers Reef, Lighthouse Reef and Turneffe Islands) Gischler (1994) and Gischler & Lomando (1999) suggested that variations in antecedent topography and exposure to waves and currents were the dominant factors infl uencing the sediment distribu tion of these three relatively small-scale carbonate platforms. In analogy with the scenario developed for the facies distribution of the inner lagoon of Mayotte (Zinke et al, 2001(Zinke et al, , 2003a, Gischler (2003) showed that the timing of refl ooding of the Pleistocene bedrock in combination with the rate of sea-level rise determined the sedimentation patterns in the lagoons of the Belize atolls.…”
Section: Comparisons With Other Platform Lagoonsmentioning
confidence: 99%
“…The juxtaposition of facies on the suggested profile is based on lithologies, facies interpretation, and also on comparison to depositional settings of intact time-equivalent platforms such as Dachstein Platform (Flügel 1981), Dolomites (Blendinger and Blendinger 1989), Triassic limestones of Sikhote-Alin (Punina 1997), Triassic carbonates of United Arab Emirates and Oman (Bernecker 1996;Maurer et al 2008), and modern isolated carbonate platforms such as Andros and other Islands of the Bahamas (Blatt et al 1980;Hine et al 1981), Kapingamarangi Atoll (Mckee et al 1959), Marshall Islands (Enewetak and Bikini Atolls, Atkinson et al (1981), the atoll system of the Maldives (Purdy and Bertram 1993) and the Banco Chinchorro (Gischler and Lomando 1999;Gischler and Möder 2009).…”
Section: Speculative Depositional Profilementioning
confidence: 99%